2016
DOI: 10.1016/j.ebiom.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Blood Epigenetic Age may Predict Cancer Incidence and Mortality

Abstract: Biological measures of aging are important for understanding the health of an aging population, with epigenetics particularly promising. Previous studies found that tumor tissue is epigenetically older than its donors are chronologically. We examined whether blood Δage (the discrepancy between epigenetic and chronological ages) can predict cancer incidence or mortality, thus assessing its potential as a cancer biomarker. In a prospective cohort, Δage and its rate of change over time were calculated in 834 bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(176 citation statements)
references
References 27 publications
6
157
1
Order By: Relevance
“…Our findings were consistent with the previous studies in different tissues [4,16]. The epigenetic clock derived from the DNAm age is robust with respect to the batch effects and can be applied to all Illumina array platforms: the EPIC chip (850K), the Illumina 450K array and the 27K array [4] and possibly measures a cell intrinsic and tissue independent epigenetic drift [46]. For blood derived DNA measured on the Illumina 450K array, the epigenetic clock algorithm provides not only several measures of age acceleration but also estimates of blood cell counts.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings were consistent with the previous studies in different tissues [4,16]. The epigenetic clock derived from the DNAm age is robust with respect to the batch effects and can be applied to all Illumina array platforms: the EPIC chip (850K), the Illumina 450K array and the 27K array [4] and possibly measures a cell intrinsic and tissue independent epigenetic drift [46]. For blood derived DNA measured on the Illumina 450K array, the epigenetic clock algorithm provides not only several measures of age acceleration but also estimates of blood cell counts.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, age acceleration computed with Horvath's epigenetic clock, together with FHL2 clock, were associated with CRC development in males [42, 43]. …”
Section: Resultsmentioning
confidence: 99%
“…In a study based on 43 cases, the risk of lung cancer was increased by an estimated 50% per five‐year age acceleration . Another small study (132 cancer cases) concluded that age acceleration was associated with increased cancer risk and shorter cancer survival . A recent study of 480 breast cancer cases and matched controls reported a 4% increase breast cancer risk per one‐year age acceleration.…”
mentioning
confidence: 99%